Effect of environmental conditions on extracellular lipases production and fungal morphology from Aspergillus niger MYA 135 - Colin, Veronica Leticia (2010)
Under the current assay conditions, lipase production in mineral medium was only detected in the presence of vegetable oils, reaching the highest specific activity with olive oil. In this way, effect of different environmental conditions on fungal morphology and olive oil‐induced extracellular lipases production from Aspergillus niger MYA 135 was studied. It was observed that addition of 1.0 g l–1 FeCl3to the medium encouraged filamentous growth and increased the specific activity 6.6 fold after 4 days of incubation compared to the control. However, major novelty of this study was the satisfactory production of an acidic lipase at initial pH 3 of the culture medium (1.74 ± 0.06 mU μg–1), since its potencial applications in food and pharmaceutical industry are highly promising